PELUANG BISNIS DI ERA COVID-19 - Atmaja, Hanung Eka; Verawati, Dian Marlina (JAB (Jurnal Akuntansi & Bisnis), 2020)
The downturned economy makes us have to look for business opportunities that can survive the Covid 19 era. These opportunities come from market needs that have not been fully met, or market problems that have not yet met a solution. These two components make several business opportunities resilient to crisis conditions and run well. Thus, marketers and entrepreneurs must find alternative solutions to market their products or services to consumers. Business people optimize online marketing and digital branding as a means of communication with their target consumers. This is certainly a very effective choice during this pandemicÂ Keywords: covid 19, on-line marketing, digital branding